Strategi Humas Polresta Denpasar dalam Pelayanan Informasi Publik - Mayos, Elisa Aprillia; Sugiarica Joni, I Dewa Ayu; Pradipta, Ade Devia (E-Jurnal Medium, 2017)
ABSTRACT In realizing the transparency of Public Information according to Undang-Undang Number 14 in year 2008 about Public Disclosure, Police of the Republic Indonesia ratified the legislation Peraturan Kapolri Number 16  in year 2010. That regulation must be executed by all the member of Polri from the central level to the regional unity, such as Polresta Denpasar, At the level of Polresta, Documentation and Information Management Carried by public relations. In carrying out the duties to provide a public informations services, the public relations of Polresta Denpasar implement a variety of public relations strategy. In analyzing it, this research is using the method or approaching strategy of Rusady Ruslan’s public relations. This is a descriptive qualitative research by using a triangulation techniques. This study has shown implementation of Polresta Denpasar run their duties and responsibility as a public relations as well as Document and Information Management officer. In practice, public relations of Polresta Denpasar  has used several of public relations strategies based on the types information which can be delivered to the public accordance with  Perkap Number 16 in year 2010. In delivering the informations indirectly, Public Realtions of Polresta Denpasar used the social media, website and email. Other than that, Public Relations of Polresta Denpasar also serves the request for indirect information by utilizing the public services of Public Information Centre (PIC). Keywords : Public Realtions, Public Information Services, Polresta Denpasar Strategy of Public Relations